True West : myth and mending on the far side of America - Quammen, Betsy Gaines (Torrey House Press, 2023)
True West explores myths of the West and how, if left unexamined, they distort the realities of the present and exacerbate polarizations. These misperceptions about land, politics, liberty, and self-determination threaten the wellbeing of western communities overrun by newcomers seeking a dream--and the country unless America recognizes the dangers of building a national identity on illusion. Betsy Gaines Quammen interrogates it all by listening, carefully, to people from varying political and cultural perspectives as she seeks to reconcile the deep anger and broad misunderstandings that linger amid myths that define and impede the West and America.